Language, Power, and Environmental Framing in Regional Electoral Discourse: A Critical Study in North Maluku - Usman, Herman; Mahmud, Adi F.; Can, Laily Ramadhany (LETS: Journal of Linguistics and English Teaching Studies, 2026)
Language plays as a powerful political tool that not only communicates policies and ideologies but also shapes public opinion, influences power relations, and directs societal development, particularly in regional electoral contexts. This study aims to investigate the linguistic strategies used by political candidates in the 2024 North Maluku Provincial Election and to analyze how these discursive practices construct environmental narratives, political legitimacy, and regional development priorities. This research employed a qualitative design applying Critical Discourse Analysis (CDA) based on Fairclough’s three-dimensional framework, encompassing textual analysis, discourse practice, and sociocultural practice. The data consisted of candidates’ campaign speeches, debate transcripts, and media reports related to environmental and political issues. The findings reveal that environmental discourse functions not only as a policy instrument but also as a strategic resource for exercising symbolic and political power. Candidates predominantly utilized positive, negative, and ambiguous linguistic constructions to promote sustainability, criticize previous administrations, and project environmental responsibility. Nevertheless, discussions concerning mining governance, corporate accountability, indigenous rights, and environmental licensing remained limited, indicating a significant gap between environmental rhetoric and concrete policy commitments. Furthermore, environmental narratives are frequently employed to legitimize political authority and shape public perceptions rather than to advance transformative environmental governance. The study highlights the intricate relationship between language, power, and environmental governance and underscores the need for more transparent, evidence-based, and policy-oriented political communication to support sustainable regional development and democratic accountability.